(untitled) (World Bulletin of Education and Learning, 2025)
This study examines the theoretical and methodological foundations for forming innovative initiatives in the worldview of youth. In the context of rapid technological change, globalization, and the digitalization of society, fostering an innovative mindset among young people has become a key priority for sustainable social development. The research highlights the socio-cultural, psychological, and pedagogical factors that shape youth perceptions, creative thinking, and readiness for innovation. It outlines the conceptual approaches to understanding youth innovation, analyzing how social environment, educational practices, and modern technological platforms contribute to the development of initiative, creativity, and entrepreneurial thinking.